DATA MINING (KLASTERISASI) PERBANDINGAN MAHASISWA YANG MENDAFTAR TERHADAP MAHASISWA YANG DITERIMA - Walhidayat Walhidayat; Mariza Devega; Susi Handayani (Universitas Lancang Kuning, 2021)
The problem with data owned by a company or agency is data as a benchmark for basic information. However, these data are generally in a developing country or companies that have not utilized the sophisticated structure of information systems in the current era still see the data as a part of a process, which results in the data being used separately as a container of information to support decision making. . There is a need for a special study conducted by the research team to look at this problem subjectively, namely by sorting out the identification of data sources into useful information for leaders or officials. There are several methods that can be used to mine data (data mining), including: Classification, Clustering, Association and various appropriate methods can be used. The results of data mining can be information that can be easily understood by policy makers in an institution, especially leaders at the Faculty of Computer Science.